Association between thyroid function, nursing home admission and mortality in community-dwelling adults over 80 years. (January 2023) - Riis, Johannes; Kragholm, Kristian; Torp-Pedersen, Christian; Andersen, Stig
Highlights: We included 272, 495 community-dwelling adults over 80 years old. Raised TSH was associated with lower risk of nursing home admission and mortality. Outcomes may be worse the first year following treatment of hypothyroidism. Abstract: Purpose: Thyroid deficiency may reduce mortality in older adults, but older adults prioritize independence over merely staying alive. We investigated the association between thyroid dysfunction and nursing home admission and all-cause mortality in community-dwelling older adults over 80. Methods: We conducted a retrospective population-based open cohort study using data from laboratory registries covering 75% of Denmark supplemented by national registries. We included all community-dwelling older adults over 80 years with a first TSH measurement between 1996 and 2019. Participants with prior thyroid disorders or medication affecting the thyroid were excluded. Participants were followed from inclusion until nursing home admission, death or loss to follow-up due to emigration. Results: We included 272, 495 participants at baseline. Median follow-time was 3.71 years in analyses of nursing home admissions and 4.00 years for all-cause mortality. Hypothyroidism was associated with lower nursing home admission (TSH 5–10 mIU/l: HR 0.85, 95% CI: 0.80–0.91, P < 0.001); TSH >10 mIU/l HR 0.68, 95% CI: 0.54–0.85, P = 0.001) and with reduced all-cause mortality (TSH >10 mIU/l: HR 0.81, 95% CI: 0.70–0.93, P = 0.002). The association between hyperthyroidism and nursing home admission was of little clinical significance while hyperthyroidism was associated with increased all-cause mortality hazard both for low (HR 1.16, 95% CI 1.13–1.19, P < 0.001) and suppressed (HR 95% CI: 1.14 1.07–1.21, P < 0.001) TSH. Conclusion: : Hypothyroidism is associated with a reduced nursing home admission hazard and to a lesser extent all-cause mortality in community-dwelling adults over 80 years, while hyperthyroidism is associated with increased all-cause mortality but not hazard of nursing home admission.